A detailed overview of quercetin: implications for cell death and liver fibrosis mechanisms - Xiong, Fei; Zhang, Yichen; Li, Ting; Tang, Yiping; Song, Si-Yuan; Zhou, Qiao; Wang, Yi (Frontiers in Pharmacology, 2024)
Background: Quercetin, a widespread polyphenolic flavonoid, is known for its extensive health benefits and is commonly found in the plant kingdom. The natural occurrence and extraction methods of quercetin are crucial due to its bioactive potential. Purpose: This review aims to comprehensively cover the natural sources of quercetin, its extraction methods, bioavailability, pharmacokinetics, and its role in various cell death pathways and liver fibrosis. Methods: A comprehensive literature search was performed across several electronic databases, including PubMed, Embase, CNKI, Wanfang database, and ClinicalTrials.gov, up to 10 February 2024. The search terms employed were “quercetin”, “natural sources of quercetin”, “quercetin extraction methods”, “bioavailability of quercetin”, “pharmacokinetics of quercetin”, “cell death pathways”, “apoptosis”, “autophagy”, “pyroptosis”, “necroptosis”, “ferroptosis”, “cuproptosis”, “liver fibrosis”, and “hepatic stellate cells”. These keywords were interconnected using AND/OR as necessary. The search focused on studies that detailed the bioavailability and pharmacokinetics of quercetin, its role in different cell death pathways, and its effects on liver fibrosis. Results: The review discusses quercetin's engagement in cell death pathways—apoptosis, autophagy, pyroptosis, necroptosis, ferroptosis, and cuproptosis—with a focus on its regulatory role in apoptosis and autophagy. The mechanisms by which quercetin influences these processes in different cell types and dosages are also examined. Furthermore, the paper examines the impact of quercetin on liver fibrosis, its interaction with hepatic stellate cells, and modulation of related signaling pathways. Conclusion: The paper provides a detailed analysis of quercetin, suggesting its significant role in modulating cell death mechanisms and mitigating liver fibrosis, underscoring its therapeutic potential.